The incremental contribution of TOEIC® Listening, Reading, Speaking, and Writing tests to predicting performance on real-life English language tasks. (April 2015) - Powers, Donald E.; Powers, Andrew
Typically, English language proficiency tests yield multiple scores – usually for each of the four traditional language domains. In order to maximize the usefulness of test scores, they may need to be accompanied by information concerning how they complement one another. Using self-assessments by some 2300 TOEIC test takers, this study aimed to show that language performance in a particular domain (speaking, for instance) can be predicted by using a test that corresponds specifically to that domain (i.e., the TOEIC Speaking test), but also that it can be even better predicted by supplementing domain-related scores with scores (e.g., TOEIC Listening scores) that do not correspond directly to the target domain. The results of a hierarchical linear regression analysis revealed that adding test scores that did not correspond directly to the target performance domain made statistically and practically significant contributions to prediction in the target domain. Thus, more precise estimates of English language proficiency in a specific domain are possible by assessing skills not only in that domain but in other related domains as well.